Study the Effects of Ataralgesia on the State of the Cardiovascular System and Ocular Tonus in Operative Ophthalmology. - Bektemirova Norbuvi Tukhtaevna (Genius Journals, 2023)
Ataralgesia is one of the types of combined pain relief and consists of the use of an ataractic and an analgesic. To date, there is limited data in the literature on the possibility of using ataralgesia during ophthalmic surgery. The effect of this method on intraocular pressure also remains unclear. The study of ataralgesia in elderly patients and with concomitant somatic diseases is of certain value.
Keywords: Droperidol; fentanyl; seduxen